Pengaruh Program Desa Wisata Terhadap Perkembangan Ekonomi Desa Dan Pelestarian Budaya Lokal - Natasya Mentari Putri Lusi; Prilia Resa Anggriana (Universitas Musamus, Merauke, Papua, 2023)
Government Regulation No. 11 of 2021 explains that the Village has the authority to manage government affairs based on the interests of the community so that the policies made are in accordance with the problems they have. Therefore, village development so that it can become a tourist village is the right program to stimulate village original income and introduce the potential of each village. This study aims to explain the influence of the village tourism program on the economic development of the village and cultural preservation. M The method that the researcher uses is the library research. Researchers take data in the form of books, journals and references that are considered appropriate to review this research. The results of this study are that there are several tourist villages that are able to improve the village economy, but there are tourist villages that have not been able to improve the village economy. This is due to the lack of stakeholder in socializing or providing understanding to the community in tourist villages in order to be able to develop the potential in their villages, as a result some village communities are unable to innovate. Cooperation between stakeholders in tourism development is a positive key for the development of tourist villages. Utilization of local culture by a village can be an attraction to foreign and local tourists. So it is very necessary to coordinate and train rural communities to be able to develop the villages they have, as well as introduce the cultural diversity that Indonesia has.